Konstrukcja i zastosowania wykresu trójkątnego - Kozyra, Cyprian (Construction and Applications of the Ternary Graph, 2006)
Mathematical principles of ternary graph construction are presented in the paper in order to make readers able to develop such graphs using only standard spreadsheet software. The main application of this graph is visualization of three categories shares in some magnitude, when these shares sum to, 100 % of magnitude. Changes of three economic sectors shares in macroeconomic magnitudes are analyzed in order to present possibilities of ternary graph application in economics.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Ekonometria (17); 2006; nr 1123, s. 42-49